MODERNISASI KURIKULUM PESANTREN DI PONPES DARUL LUGHAH WAL KAROMAH - Mohamad Solihin (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2022)
In this modern era pesantren are required to modernize every aspect of the educational aspects especially with the purpose of pesantren able to compete with other institutions both in quality and quantity of education quality. This condition occurs in Pesantren Darul lughah Wal Karomah that change patterns towards modern education. The purpose of this research includes the history of the modernization of education and how the modernization of education pesantren in Darul lughah Wal Karomah.This research used a qualitative approach, whereas other types of research using case studies. The collection of data by observation, interviews, documentation. Analysis of the data by (1) Collection of Data (2) Reduction of Data (3) Presentation of Data (4) Withdrawal of Conclusion. Data validity checking with (1) credibility (2) transferability (3) Dependability (4) Confirmability. Results of this study showed that the old teaching system that is maintained tends to lag, and the demands of a society increasingly complex and varied. While the form of modernization of education include institutional aspects, curriculum, learning and functional aspects of pesantren. Modernization of the institutional aspects, ie from individual leadership (scholars) to a collective system (foundation) with a clear division of labor. In the aspect of the curriculum, the introduction of a curriculum created by Kemdikbud and Kemenag. In the aspect of teaching, namely from system to system halakah classical / schooling by teaching methods that apply to modern educational institution, such as a lecture, question and answer, discussion, demonstration, drama, recitation, and teamwork.